The Role Of The Quran In Regulating The Government System - Muhammad Roni (Prodi Tata Negara (Siyasah) IAIN Langsa, 2022)
Siyāsah dusturiyāh has so far not been revealed in detail. In the stage of world history, it can be seen that the good and bad of the country depends on the system of government. The Koran has expressly established the necessity of government.)” very interesting to study. Data analysis was carried out using thematic (Maudhu'ï). In the thematic method all the relevant verses are collected, then studied in more depth from various aspects related to them. In this method it is also supported by postulates or truths that can be scientifically and rationally accounted for. Based on the method used, the Koran explains that leadership in siyāsah dusturiyāh can be adapted to each age. Leadership in Islam is a fitrah for every human being as well as motivating islamic leadership. Man is mandated by Allah Almighty to become caliph to lead people in religion and the world, as well as to govern the people and maintain religion and politics. The system of government referred to in the Koran consists of five: namely Imamah, The People and Their Obligations, Bai'at, Ahl al-Hall Wa al-Aqd, and Wizarah.